Colonization factor antigen CFA/IV (PCF8775) of human enterotoxigenic Escherichia coli: nucleotide sequence of the CS5 determinant. - Clark, C A (1992)
Human enterotoxigenic Escherichia coli isolates expressing the colonization factor antigen CFA/IV (previously designated PCF8775) produce plasmid-encoded CS5 fimbriae. The nucleotide sequence of the region encoding the major CS5 fimbrial subunit was determined. The subunit is synthesized as a precursor of 203 amino acids (20.85 kDa) with a mature protein of 181 amino acids corresponding to a size of 18.6 kDa. The CS5 subunit shows homology to the corresponding component of porcine enterotoxigenic E. coli F41, particularly within the signal sequence and at the carboxy terminus.